Impact of Oral Glucosamine-Chondroitin-Methylsulfonylmethane Supplementation on Functional Recovery in Dogs with Diaphyseal Fractures - Palli, Ravi Kumar; Rajapanthula, Mahesh; Devarakonda, Srikala; Veneela, Tejaswani; Vaddadi, Devi Prasad (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
This study evaluated the effect of oral Glucosamine HCl, Chondroitin sulphate, and Methylsulfonylmethane (MSM) on fracture healing in dogs treated with minimally invasive external skeletal fixation (ESF). Twelve dogs with diaphyseal fractures of the radius-ulna or tibia fibula were randomly assigned to two equal groups: Group I served as control, and Group II received oral Flexirun tablets (glucosamine, chondroitin, and MSM) for two months. Lameness and radiographic healing were assessed on the 7th, 15th, 30th, and 60th postoperative days. All dogs showed progressive improvement, but Group II demonstrated faster functional recovery and earlier callus formation, with significant differences in healing scores at day 30. By day 60, both groups achieved near-complete union, with excellent outcomes in most cases. The findings indicate that ESF provides effective fracture stabilization, while adjunctive glucosamine, chondroitin, and MSM accelerate recovery, reduce stiffness, and enhance limb function during the critical early and mid-recovery periods. Nutraceutical supplementation may therefore serve as a valuable adjunct in canine fracture management.